2022
DOI: 10.3390/ijerph191912318
|View full text |Cite
|
Sign up to set email alerts
|

Association of Workplace Culture of Health and Employee Emotional Wellbeing

Abstract: The study aimed to examine associations between workplace culture of health and employee work engagement, stress, and depression. Employees (n = 6235) across 16 companies voluntarily completed the Workplace Culture of Health (COH) Scale and provided data including stress, depression, and biometrics through health risk assessments and screening. We used linear regression analysis with COH scores as the independent variable to predict work engagement, stress, and depression. We included age, gender, job class, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The Workplace COH Scale is a valid and reliable measure developed in 2015 that has been used in the industry and research. 12,13,16,24 The Workplace COH Scale assesses workplace COH through the following five domains: senior leadership and policies, programs and rewards, quality assurance, supervisor support, and coworker support. Research has shown that senior leadership plays a key role in sustaining an environment that supports health.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The Workplace COH Scale is a valid and reliable measure developed in 2015 that has been used in the industry and research. 12,13,16,24 The Workplace COH Scale assesses workplace COH through the following five domains: senior leadership and policies, programs and rewards, quality assurance, supervisor support, and coworker support. Research has shown that senior leadership plays a key role in sustaining an environment that supports health.…”
mentioning
confidence: 99%
“…Workplace culture of health (COH) can be defined as the combined influence of the physical and social environment on behaviors and attitudes related to health and well-being in the workplace 12,13 . Theories such as the social-ecological model support influencing culture as an effective way to target population health.…”
mentioning
confidence: 99%
See 3 more Smart Citations